Relation between αs1-casein, proteolytic activity and composition of milk from Swedish goats - Larsson, Emma (2021)
In the recent decade, locally produced food has gained in interest among Swedish consumers. Consumer values for buying local food has to do with concerns about diversity, purity and authenticity of food as well as a desire to support rural areas. One type of product that has gained in interest is locally produced goat cheese. The goat industry in Sweden is small scaled, however, steadily increasing. In goats, the CSN1S1 gene regulates the expression of the protein αS1-casein (αS1-CN). This casein has been found to be important for the cheese yield. Over the years, breeding animals have been imported to Sweden from Norway. Historically a high frequency of the Norwegian goat population carried a polymorphism at the CSN1S1 gene. This polymorphism, called the Norwegian null allele (D), leads to zero or heavily reduced expression of αS1-CN. Consequently, in Sweden, the number of goats homozygous for the Norwegian null allele, increased dramatically. This study aimed to investigate how the expression of αS1-CN and the genetic profile of the CSN1S1 gene influence the proteolytic activity and milk composition of milk from Swedish dairy goats. Within the study, milk samples from 75 goats were analysed for total proteolysis, plasmin activity (PL) and plasminogen derived activity (PG). Total proteolysis was determined by a luminescent method, measuring the amount of free terminal amino groups present in the milk. For PL and PG analysis, a spectrophotometric method with chromogenic substrate was used, where PG was activated with urokinase. The results for gross composition, somatic cell count, protein profile and genotype were also included in this investigation. Milk samples were grouped according to level of αS1-CN (low 0-6.9% and medium-high 7-25% of total protein) and genotype (DD, DG and DA/AG/AA). For the statistical analysis, Pearson and Spearman correlations were applied. The groups were compared with two-sample T-test and one-way ANOVA. The frequency of individuals homozygous for the Norwegian null allele (DD) was 58%, and only 15% of the studied goats carried an A allele. A significant association was found between the level of αS1-CN in the milk and allele combination (p <0.001). Moreover, a significant positive correlation was found between αS1-CN with total protein (p ≤ 0.001). Total protein was negatively correlated with total proteolysis (p ≤ 0.001) and PG (p ≤ 0.01) and positively correlated with PL (p ≤ 0.05). However, no correlation between total proteolysis and PL was found. SCC, pH and FFA were significantly higher among the genotype homozygous for the null allele (DD) compared to genotypes with an A allele (p ≤ 0.05). This may have effects on milk processability and the sensory properties of the processed dairy product. Further research is needed to understand the relationship between αS1-CN and proteolytic activity, for example including additional parameters within the plasmin-plasminogen system such as the activity of plasminogen activators and plasmin inactivators. In addition, the bacterial status of the milk could be included.